2014
DOI: 10.1111/cmi.12257
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbiota stimulate systemic neutrophil migration through induction of Serum amyloid A

Abstract: Summary Neutrophils serve critical roles in inflammatory responses to infection and injury, and mechanisms governing their activity represent attractive targets for controlling inflammation. The commensal microbiota is known to regulate the activity of neutrophils and other leucocytes in the intestine, but the systemic impact of the microbiota on neutrophils remains unknown. Here we utilized in vivo imaging in gnotobiotic zebrafish to reveal diverse effects of microbiota colonization on systemic neutrophil dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 70 publications
7
90
0
1
Order By: Relevance
“…Serum amyloids are up-regulated by proinflammatory signals (e.g., IL-1, TNF-α, and IL-6), which are increased during Yersinia infection. They participate in the systemic modulation of innate and adaptive immune responses (e.g., T H 17 responses and migration/activation of monocytes, neutrophils, and T cells) (35)(36)(37)(38). Moreover, they have antimicrobial activity and induce expression of matrix metalloproteases, chitinase-like proteins, and collagenases that are pivotal for tissue remodeling after injury (39).…”
Section: Resultsmentioning
confidence: 99%
“…Serum amyloids are up-regulated by proinflammatory signals (e.g., IL-1, TNF-α, and IL-6), which are increased during Yersinia infection. They participate in the systemic modulation of innate and adaptive immune responses (e.g., T H 17 responses and migration/activation of monocytes, neutrophils, and T cells) (35)(36)(37)(38). Moreover, they have antimicrobial activity and induce expression of matrix metalloproteases, chitinase-like proteins, and collagenases that are pivotal for tissue remodeling after injury (39).…”
Section: Resultsmentioning
confidence: 99%
“…57,58 We found that treating mice with broad-spectrum antibiotics accelerated the apoptotic cell death and clearance of circulating neutrophils, comprising 2 essential steps in phagocyte turnover. Several previous studies have documented effects of the microbiota on distinct aspects of neutrophil biology, including stimulation of neutrophil development in the bone marrow, [22][23][24] trafficking to inflamed tissues, 25 and bactericidal capacity. 27 Recently, Toll-like receptor-dependent and MyD88-dependent signals from the microbiota were found to drive the phenotypic aging of circulating neutrophils, corresponding with enhanced inflammatory capacity and trafficking from the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] However, mature phagocytes from animals raised germ-free or treated with antibiotics also exhibit a range of functional defects, including impaired trafficking to tissues, production of reactive oxygen species, and bactericidal capacity. [25][26][27] Given that the commensal flora can influence phagocyte function in the periphery, we hypothesized that steady-state microbial signals may enhance the lifespan of circulating neutrophils and that this effect may extend to other short-lived, circulating phagocytes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mice colonized with segmented filamentous bacteria produce more serum amyloid A (SAA) which act on DCs to skew toward a Th17 phenotype [Ivanov et al 2009]. Microbiota can induce SAA, leading to neutrophil migration, which may also be partly mediated by DC activity [Kanther et al 2014]. Further, it has been demonstrated that induction of SAA is mediated by bacterial adhesion to epithelial cells, leading to downstream Th17 cell responses via CD11c + cells, which were critical for the response [Atarashi et al 2015].…”
Section: Dendritic Cell Modulationmentioning
confidence: 99%